Improvement of the Vietnamese Diet for Women of Reproductive Age by Micronutrient Fortification of Staples Foods and Condiments - Laillou, Arnaud (Public Library of Science, 2012)
BACKGROUND: A micronutrient survey carried out in 2010 among randomly selected Vietnamese women in reproductive age indicated that anemia and micronutrient deficiencies are still prevalent. The objective of this study was thus to analyze the dietary micronutrient intakes of these women, to select the food vehicles to be fortified and to calculate their contributions to meet the recommended nutrient intake (RNI) for iron, zinc, vitamin A and folic acid. MAIN FINDINGS: Consumption data showed that the median intake was 38.4% of the RNI for iron, 61.1% for vitamin A and 91.8% for zinc. However, more than 50% of the women had daily zinc consumption below the RNI. Rice and vegetable oil were consumed daily in significant amounts (median: 320.4 g/capita/day and 8.6 g/capita/day respectively) by over 90% of the women, making them suitable vehicles for fortification. Based on consumption data, fortified vegetable oil could contribute to an additional vitamin A intake of 27.1% of the RNI and fortified rice could increase the intake of iron by 41.4% of the RNI, zinc by 15.5% and folate by 34.1%. Other food vehicles, such as fish and soy sauces and flavoring powders, consumed respectively by 63% and 90% of the population could contribute to increase micronutrient intakes if they are properly fortified and promoted. Wheat flower was consumed by 39% of the women and by less than 20% women from the lowest socioeconomic strata. CONCLUSION: The fortification of edible vegetable oils with vitamin A and of rice with iron, zinc and folic acid are the most promising fortification strategies to increase micronutrient intakes of women in reproductive age in Vietnam. While rice fortification will be implemented, fortification of fish and soy sauces with iron, that has been proven to be effective, has to be supported and fortification of flavouring powders with micronutrients investigated.